A Randomized Trial to Investigate Needle Redirections/Reinsertions Using a Handheld Ultrasound Device Versus Traditional Palpation for Spinal Anesthesia in Obese Women Undergoing Cesarean Delivery. Issue 4 (21st December 2022) - Weiniger, C.F.; Carvalho, B.; Ronel, .; Greenberger, C.; Aptekman, B.; Almog, O.; Kagan, G.; Shalev, S.
Abstract : ( Int J Obstet Anes . 2022;49:103229) Compared with palpation (PAL), using ultrasound to identify the insertion point in neuraxial procedures is associated with higher success rates. Handheld ultrasound (H-US) devices use an algorithm to analyze images, rather than clinician interpretation with console or laptop ultrasound. These devices may be especially useful in obese obstetric patients. This study aimed to compare H-US and PAL in terms of number of reinsertions and redirections in obese patients undergoing spinal anesthesia for cesarean delivery.